Wind as an energy source of polar atmospheric gravity waves - Alla Fedorenko; Evgen Kryuchkov; Anna Voitsekhovska (Ukrainian Antarctic Journal, 2025)
We investigated the properties of atmospheric gravity waves (AGW) in the areas of polar thermosphere wind systems using satellite measurement data. It was established that AGWs systematically propagate in the direction from night to day towards the wind. The dependence of the wave amplitude on the headwind wind velocity was studied. In an oncoming non-uniform wind flow, wave amplitudes increase due to energy exchange with the medium. As a result, such large-amplitude AGWs are predominant in observations in the polar thermosphere. Therefore, wind flow regions can be considered a source of energy for AGW. The frequencies of polar AGW were determined from satel lite measurements. The obtained frequency values for different polar orbits of the Dynamics Explorer 2 satellite are very close to the Brunt-Väisälä (BV) frequency. This indicates the filtering of the wave spectrum in the non-uniform wind flow. The results allow us to explain the main properties of AGW in the polar thermosphere observed from the satellite and compare them with ground-based measurements. When comparing the results of satellite and ground measurements of AGW characteristics, background atmospheric flows must be taken into account. Thus, the frequencies of AGW determined from satellite data are close to the Brunt-Väisälä frequency. However, a ground observer will register such waves as very low-frequency disturbances. It can be assumed that some of the observed cases of large-scale AGW are medium-scale disturbances propagating against the background of strong winds. Under increased geomagnetic activity, the speeds of polar vortices increase, accompanied by an increase in energy transfer from the wind. Therefore, AGWs play an important role in the energy balance of the polar atmosphere, redistributing the energy of disturbed wind flows in the vertical direction.